Young children becoming curriculum Deleuze, Te Whariki and curricular understandings - Sellers, Marg (Contesting early childhood, 2013)
This book contests a tradition and convention in educational thinking that dichotomizes children and curriculum, by developing the notion of re(con)ceiving children in curriculum. By presenting an innovative research project, in which she worked with children to share their understandings of the internationally renowned Te Whariki curriculum, Marg Sellers explores what curriculum means to children and how it works, as demonstrated in games they played. In generating different ways for thinking, the author draws upon her work with the philosophical imaginaries of Gilles Deleuze and Felix Guattari, whose ideas shape both the content and the non-linear structure of this book. Topics covered include: rhizomes, rhizo-methodology and rhizoanalysis, plateaus--Book jacket.